Best Practices in the Implementation of Research Infrastructure in the Academic Environment: Shortcomings and Revisions - Lorenz, Michal; Juranová, Ema; Konečný, Michal; Kubelková, Hana; Wölfelová, Veronika (International Journal of Knowledge Content Development & Technology, 2023)
The Digitalia MUNI ARTS - a local node of the LINDAT/CLARIAH-CZ research infrastructure at the Faculty of Arts of Masaryk University constitutes a repository in the Islandora system. It is used for long-term preservation of research data together with their research environment in the form of digital platforms. We transfer the digital outputs of humanities scholars research to the repository according to a set plan, which is based on best practice recommendations for project management and digital curation. In this paper, we present how the results of interviews with platform developers and infrastructure stakeholders translate into the curation workflow, and a resulting model for migrating digital platforms to the repository. Reflecting on three types of problems we encountered during the implementation of platforms into the repository - communication problems, problems of external dependence, and management problems - we describe a modification of the migration process. We present six recommendations for repository administrators and curators in an academic setting - holding an introductory meeting with developers, researching significant and relevant theories of knowledge domain, consulting license experts, prioritizing requirements, and preparing handover protocol and progress reports.